Sustainable Packaging: Bioplastics as a Low-Carbon Future Step for the Sustainable Development Goals (SDGs) - Basnur, Jumharijah; Putra, Muhammad Fakhri Ferdian; Jayusman, Shabrina Vee Amelia; Zulhilmi, Z. (ASEAN Journal for Science and Engineering in Materials, 2024)
In recent years, the issue of desirability or sustainability has dominated the global conversation. This research focuses on designing solutions to environmentally detrimental carbon footprints, contributing to achieving SDGs climate action with a focus on sustainable packaging. Through a qualitative approach and methodological literature study, we analyzed that the use of sustainable packaging uses fewer raw materials and is more energy efficient, such as recycled plastic (bioplastic) and alternative materials that require less energy in their production. The results of this research show that the use of bioplastics has a real impact on the carbon footprint. Natural bioplastic materials can be degraded because the molecular structure of the raw material is crystalline so it is more fragile and more easily degraded than conventional plastic. Sustainable Packaging is an important future step towards low carbon.